2014
DOI: 10.1002/glia.22748
|View full text |Cite
|
Sign up to set email alerts
|

The EIIIA domain from astrocyte‐derived fibronectin mediates proliferation of oligodendrocyte progenitor cells following CNS demyelination

Abstract: Central nervous system remyelination by oligodendrocyte progenitor cells (OPCs) ultimately fails in the majority of multiple sclerosis (MS) lesions. Remyelination benefits from transient expression of factors that promote migration and proliferation of OPCs, which may include fibronectin (Fn). Fn is present in demyelinated lesions in two major forms; plasma Fn (pFn), deposited following blood‐brain barrier disruption, and cellular Fn, synthesized by resident glial cells and containing alternatively spliced dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 77 publications
2
32
0
Order By: Relevance
“…The apparent redundancy of plasma fibronectin, despite its well-documented ability to promote OPC proliferation in vitro , was accounted for by the limited blood-brain barrier break-down in the employed model. Importantly, the deletion of both plasma and astrocyte Fn did not affect the overall extent of OLG differentiation and remyelination (Stoffels et al, 2015), an observation that is consistent with the notion that recruitment of OPCs may not always be the rate-determining factor for remyelination (Franklin and Goldman, 2015). …”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…The apparent redundancy of plasma fibronectin, despite its well-documented ability to promote OPC proliferation in vitro , was accounted for by the limited blood-brain barrier break-down in the employed model. Importantly, the deletion of both plasma and astrocyte Fn did not affect the overall extent of OLG differentiation and remyelination (Stoffels et al, 2015), an observation that is consistent with the notion that recruitment of OPCs may not always be the rate-determining factor for remyelination (Franklin and Goldman, 2015). …”
Section: Introductionsupporting
confidence: 74%
“…Upon CNS injury, two forms of fibronectin, which differ in cellular source and the presence/absence of alternatively spliced domains, can be found: plasma fibronectin leaking through a damaged blood-brain-barrier and cellular fibronectin released by predominantly astrocytes (Stoffels et al, 2013). Genetic ablation of plasma and/or astrocyte fibronectin ( Fn ) in a model of lysolecithin-induced demyelination revealed a role of predominantly astrocyte fibronectin on OPC proliferation, but not migration (Stoffels et al, 2015). The apparent redundancy of plasma fibronectin, despite its well-documented ability to promote OPC proliferation in vitro , was accounted for by the limited blood-brain barrier break-down in the employed model.…”
Section: Introductionmentioning
confidence: 99%
“…Fibronectin aggregates have also been observed in both chronic EAE and chronically demyelinated MS lesions, and injection of astrocyte-derived fibronectin aggregates into experimentally demyelinated lesions resulted in reduced OPC differentiation and remyelination (Stoffels et al, 2013a). In addition, knockout of astrocyte-derived fibronectin resulted in reduced OPC proliferation following demyelination (Stoffels, Hoekstra, Franklin, Baron, & Zhao, 2015). In addition, knockout of astrocyte-derived fibronectin resulted in reduced OPC proliferation following demyelination (Stoffels, Hoekstra, Franklin, Baron, & Zhao, 2015).…”
Section: Fibronectinmentioning
confidence: 97%
“…However, Milner et al (Milner et al, 1996) show fibronectin promotes migration of OPCs to a similar extent in vitro compared with laminin. In addition, knockout of astrocyte-derived fibronectin resulted in reduced OPC proliferation following demyelination (Stoffels, Hoekstra, Franklin, Baron, & Zhao, 2015).…”
Section: Fibronectinmentioning
confidence: 99%
“…Increasing evidences indicated that astrocytes play critical roles in OPCs and OLs survival, maturity and myelination through the intercellular crosstalk (Fischer et al 2014;Pang et al 2013;Stoffels et al 2015;Su et al 2011). The heterogeneous phenotypes of astrocytes are shown to relevantly affect the myelination capacity.…”
Section: Crosstalk Between Astrocytes and Oligodendrocyte Lineage Cellsmentioning
confidence: 97%